To Restore Faith and Trust: Justiceand Biological Accessto Cellular Therapies - Greene, Mark (The Hastings Center report, 2006)
Stem cell therapies should be available to people of all ethnicities. However, most cells used in the clinic will probably come from lines of cells stored in stem cell banks, which may end up benefiting the majority group most. The solution is to seek additional funding, earmarked for lines that will benefit minorities and offered as a public expression of apology for past discrimination.